Electrical properties of lightly Ga-doped ZnO nanowires. (31st October 2017) - Alagha, S; Heedt, S; Vakulov, D; Mohammadbeigi, F; Kumar, E Senthil; Schäpers, Th; Isheim, D; Watkins, S P; Kavanagh, K L
Abstract: We investigated the growth, crystal structure, elemental composition and electrical transport characteristics of ZnO nanowires, a promising candidate for optoelectronic applications in the UV-range. Nominally-undoped and Ga-doped ZnO nanowires were grown by metal-organic chemical vapor deposition. Photoluminescence measurements confirmed the incorporation of Ga via donor-bound exciton emission. With atom-probe tomography we estimated an upper limit of the Ga impurity concentration ( 10 18 cm − 3 ). We studied the electrical transport characteristics of these nanowires with a W-nanoprobe technique inside a scanning electron microscope and with lithographically-defined contacts allowing back-gated measurements. An increase in apparent resistivity by two orders of magnitude with decreasing radius was measured with both techniques with a much larger distribution width for the nanoprobe method. A drop in the effective carrier concentration and mobility was found with decreasing radius which can be attributed to carrier depletion and enhanced scattering due to surface states. Little evidence of a change in resistivity was observed with Ga doping, which indicates that the concentration of native or background dopants is higher than the Ga doping concentration.